17. HEMATOLOGICAL DISEASE PATTERNS AT NGHE AN FRIENDSHIP GENERAL HOSPITAL PERIOD 2023-2024 (Vietnam Journal of Community Medicine, 2025)
Objective: To characterize the spectrum of hematologic disorders diagnosed at Nghe An General Friendship Hospital during the period from 2023 to 2024.Materials and methods: A descriptive cross-sectional study was conducted. A total of 874 patients undergoing initial evaluation including complete blood count, bone marrow cytology, and/or histopathological examination of bone marrow biopsy at Nghe An General Friendship Hospital from 2023 to 2024 were enrolled.Results: The mean age of patients was 77.5 years, the incidence of the disease is equal in men and women. Bone marrow pathology was identified in 52.2% of cases. Among these, the most prevalent group was myelodysplastic syndromes (MDS) (32.3%), followed by chronic myeloproliferative neoplasms (MPNs) (23.9%), aplastic anemia (12.9%), acute leukemia (12.7%), and multiple myeloma (7.3%). Other diagnoses included chronic lymphocytic leukemia (1.3%), MDS/MPN overlap syndromes (1.1%), metastatic carcinoma involving bone marrow (0.4%), bone marrow-infiltrating lymphoma (0.4%), bone marrow necrosis (0.2%), and acute lymphoblastic leukemia (0.2%). Within the malignant chronic MPN group, essential thrombocythemia was the most frequent entity (47.7%), followed by polycythemia vera (34%), chronic myeloid leukemia (16.5%), and primary myelofibrosis (1.8%).Conclusion: More than half of the 874 patients were diagnosed with bone marrow-related hematologic disorders. The most commonly encountered disease groups were myelodysplastic syndromes and malignant chronic myeloproliferative neoplasms.
Keywords: Chronic hematologic malignancies, bone marrow metastases from solid tumors.